Effect of the Number and Distribution of Circular Holes on the Damage and Fracture of Limestone Using PFC2D. (5th December 2022) - Liu, Handong; Liu, Shuai; Liu, Haining; Fu, Yunyou; Kang, Minglei; Bai, Zhe; Xu, Jianglong; Zheng, Chao
Abstract : The common occurrence of various number and distribution of hole flaws complicates the mechanical behavior and fracture mode of the rock masses that contain them. This study develops seven numerical models of limestone samples with different numbers and distributions of circular hole flaws using 2-D particle flow discrete element code (PFC2D) to investigate their impact on the mechanical properties of limestone while maintaining the same flaws area. In addition, it analyzes the effect of these factors on the mesomechanical features of each model, including the characteristic stress values (peak stress, crack initiation, and damage stress), crack evolution, stress, and displacement field. The results showed that the peak stress, crack initiation, and damage stress of the single-hole model are between those of multihole models. As the arrangement of dip angle increases, the peak stress, crack initiation, and damage stress of models with the same number of multihole flaws exhibit a V-shaped change. The characteristic stress values are the largest when the holes are vertically aligned. Model differences in crack development path, shape, and number, as well as stress concentration area and failure mode, are primarily due to the number and distribution of holes. The circular holes are arranged at approximately 45°, and the greater the number of defects, the more likely the model is to fail. The study's findings can provide support and reference for the research system of deformation and failure of rock mass with hole flaws.